The COMPARATIVE STUDY ON DEVELOPMENT INEQUALITY WEST JAVA USING WILLIAMSON INDEX - PRATIWI, RESI; Try Waluyo, Adiet; Indrayanti, Wiwin; Purwaningsih, Fita (Salam (Islamic Economics Journal), 2026)
This study examines the magnitude of development inequality across 27 districts and municipalities in West Java during the period 2015–2024, employing the Williamson Index as the primary analytical tool. Utilizing a descriptive qualitative approach, the research assesses both macro-level disparities and region-specific characteristics. The findings indicate an average inequality index of 0.7180, categorized as high. The highest level of inequality was observed in 2020 (0.7462), while the lowest was recorded in 2019 (0.6902). Comparative analysis reveals that regencies experience greater average inequality (0.7548) than municipalities (0.6633), with the widest gap of 0.1547 occurring in 2020. This divergence highlights how limited access to infrastructure and public services in regencies intensifies developmental imbalances. Moreover, fluctuating economic growth reaching its lowest point in a decade in 2020 illustrates that expansion alone does not necessarily reduce inequality. Over the past decade, West Java has remained unable to transition into the moderate or low inequality categories. Consequently, development inequality persists as a critical structural challenge, requiring urgent policy prioritization to foster more equitable regional progress and improve the distribution of services across the province.